Smokers, smoking deprivation and time discounting - Shoko Yamane; Hiroyasu Yoneda; Taiki Takahashi; Yoshio Kamijo; Yasuhiro Komori; Fumihiko Hiruma; Yoshiro Tsutsui (Osaka University, Institute of Social and Economic Research (ISER), 2011)
This paper investigates whether smokers exhibit greater time discounting than non-smokers, and how short-term nicotine deprivation affects time discounting. A unique feature of our experiment is that our subjects receive rewards not only of money, but also of actual tobacco. This is done in order to elicit smokers' true preferences. Smokers are more impatient than non-smokers, consistent with previous studies. Additionally, nicotine deprivation makes smokers even more impatient. These results suggest that nicotine concentration has different effects on time preferences in the short and long runs.
Keywords: D03; D90; I10; Q57; 330; time discounting; nicotine concentration; smoking deprivation; panel logit analysis; economic experiment; Rauchen; Zeitpräferenz; Test